Aplicação de um instrumento para avaliação objetiva da habilidade para alimentação oral de recém-nascidos pré-termo - Berwig, Luana Cristina (2013)
There is no consensus in the literature about the best tool to assess the oral feeding skills of preterm infants reason why researchers have been trying to figure out what is the most efficient. Objective: To investigate the application of an objective tool to assess the oral feeding skills of preterm infants. Methods: The sample consisted of 44 preterm infants, divided into two strata according gestational age (27 between 30-33 and 17 between 34-36 weeks of gestational age). After medical prescription to begin oral feeding, the objective assessment of the oral feeding skills at first bottlefeeding was made by a speech therapist. Proficiency (percentage of milk taken in the first five minutes in relation to total prescribed) and rate of milk transfer (volume of milk accepted orally in relation to the time required for it) were obtaied. From the combination of these two variables the oral feeding skills were graded in levels as proposed by Lau and Smith (2011). The results were statistically analyzed, considering a significance level of 5% (p <0.05). Results: Significant differences were evidenced between the oral feeding skills levels and feeding duration, proficiency, rate of milk transfer, oral feeding performance and days of hospitalization. Conclusion: We concluded that the tool proposed by Lau and Smith (2011) is a good objective indicator of the oral feeding skills of preterm infants.